Magic & hypersystems : constructing the information-sharing library - Billings, Harold, 1931- (American Library Association, 2002)
Taking a penetrating look at the history of information systems, from the past to the present and future, veteran librarian and digital network expert Harold Billings discusses the impact of the information revolution on libraries and information hubs worldwide. Tracing the seminal origins of the Web to the new, borderless access to information, Magic and Hypersystems is a powerful meditation on how libraries can not only fit into the digital information flow but also capitalize on their role in it. Billings connects the dots from sixteenth century knowledge organization--based on ''magic, '' im.